Influence of water and oil quenching on the microstructure and mechanical properties of S45C steel - Enok Mardiah; Suharmadi Suharmadi; Farrah Anis Fazliatul Adnan; Jong Soo Rhyee; Dianta Ginting (SINERGI, 2026)
S45C steel, commonly used in industrial applications due to its balanced mechanical properties, often requires further heat treatment to meet specific functional requirements. However, selecting the appropriate quenching medium, such as water or oil, significantly affects the steel's microstructural and mechanical outcomes, creating a trade-off between hardness and strength. This study systematically investigates the influence of water and oil quenching on the microstructure, hardness, and tensile properties of S45C steel. Specimens were austenitized at 900°C, held for 45 minutes, and rapidly quenched in either water or oil. Mechanical tests included hardness measurement using the Rockwell C (HRC) scale, ultimate tensile load, and ultimate tensile strength testing conducted on a universal testing machine. The Hall-Petch theory was applied to analyze the relationship between grain size and hardness. Results demonstrate significant improvements in mechanical properties with both quenching methods. Water quenching achieved the maximum hardness (55.7 HRC) compared to untreated steel (25.6 HRC), representing a 118% enhancement, with an ultimate tensile strength of 891.4 MPa versus 632.3 MPa for the baseline (41% improvement). Oil quenching demonstrated a moderate increase in hardness to 42.9 HRC (68% enhancement) while achieving a superior ultimate tensile strength of 1041.3 MPa (65% improvement). These findings establish critical trade-offs in quenching media selection: water quenching maximizes hardness for wear-resistant applications, while oil quenching optimizes tensile strength for structural components requiring superior load-bearing capacity.